Significance of Wnt/β-Catenin Signal Activation for Resistance to Neoadjuvant Chemoradiotherapy in Rectal Cancer - Shoji Miyako; Takeru Matsuda; Yu-ichiro Koma; Takahiro Koide; Ryuichiro Sawada; Hiroshi Hasegawa; Kimihiro Yamashita; Hitoshi Harada; Naoki Urakawa; Hironobu Goto; Shingo Kanaji; Taro Oshikiri; et al. (Biomedicines, 2023)
Although a therapeutic response to neoadjuvant chemoradiotherapy (NACRT) is important to improve oncological outcomes after surgery in patients with locally advanced rectal cancer, there is no reliable predictor for this. The Wnt/β-catenin signal is known to be crucial for the tumorigenesis of colorectal cancer. This study aimed to investigate the association of Wnt/β-catenin signal activation with a pathological response to NACRT. The immunohistochemical expression of nuclear and membranous β-catenin was analyzed in biopsy samples obtained from 60 patients with locally advanced rectal cancer who received curative surgery following NACRT. The association of Wnt/β-catenin signal activation with their clinical outcomes was investigated. Notably, the body mass index of these patients was significantly higher in the low nuclear β-catenin expression group. Moreover, patients in the high nuclear β-catenin expression group tended to have more advanced disease and a higher rate of positive vascular invasion than those in the low expression group. Furthermore, the rate of good histological responses was significantly higher in the low nuclear β-catenin expression group (72% vs. 37.1%, p < 0.01). Overall, relapse-free survival tended to be better in patients with low nuclear/high membranous β-catenin expression (n = 9) than in other individuals (n = 51) (p = 0.093 and p = 0.214, respectively). Activation of the Wnt/β-catenin signal pathway represented by nuclear β-catenin accumulation was significantly associated with a poor response to NACRT in patients with rectal cancer. Analysis of nuclear β-catenin accumulation before starting treatment might help predict the therapeutic response to NACRT.